Temporal trend analysis of avoidable mortality in Taiwan, 1971-2008: overall progress, with areas for further medical or public health investment - Chen, Brian K (BioMed Central, 2013)
BACKGROUND: Avoidable mortality (AM), or “unnecessary untimely death,” is considered an indicator of health care quality. We investigated trends in the age-standardized mortality rates (ASMRs) and associated standard expected years of life lost (SEYLL) for deaths amenable to medical care or public health measures in Taiwan from 1971-2008, with an emphasis on identifying areas where additional medical or public health investment may help reduce the burden of AM. METHODS: Taiwan’s ASMRs per 100,000 for AM and other causes of death were calculated using data from the National Death Certificate Registry in five-year bins from 1971 to 2008. SEYLL rates per 100,000 were calculated annually from 1971 to 2008 using the same data source. RESULTS: ASMR for almost all AM and other causes of death declined dramatically from 1971 to 2008 except for lung cancer (16.6% and 7.4% increase among men and women, respectively) and breast cancer (109.8% increase among women). In the same period, SEYLL due to lung cancer increased from 269.2 to 555.7 for men and 249.7 to 342.5 for women. For women, SEYLL due to breast cancer increased from 263.5 in 1971 to 659.3 in 2008. There were gender-specific differences in the reduction (or increase) in AM rates, with women showing larger rates of reduction or smaller rates of increase. Among men, AM fell by 65.9% from 1971-1975 to 2006-2008, and deaths from other causes increased by 15.6%. Among women, AM and deaths from other causes fell by 80.8% and 59.8% respectively. SEYLL decreased, respectively among males and females, from 23,147.3 and 24,081.1 in 1971 to 11,261.8 and 5,929.6 in 2008. CONCLUSION: From 1971 to 2008, Taiwan experienced a dramatic reduction in most AM and corresponding SEYLL except for lung cancer (for both males and females) and breast cancer (for females). Additional effort should be devoted to public health measures to combat the rising prevalence of smoking in Taiwan, which may be responsible for the increasing AM from lung cancer. If AM in breast cancer continues unabated in the future, greater policy emphasis on the early detection and treatment of breast cancer may also be warranted.